ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2020
DOI: 10.1109/icassp40776.2020.9054288
|View full text |Cite
|
Sign up to set email alerts
|

One-Bit DoA Estimation via Sparse Linear Arrays

Abstract: Direction of Arrival (DoA) estimation using Sparse Linear Arrays (SLAs) has recently gained considerable attention in array processing thanks to their capability to provide enhanced degrees of freedom in resolving uncorrelated source signals. Additionally, deployment of onebit Analog-to-Digital Converters (ADCs) has emerged as an important topic in array processing, as it offers both a low-cost and a low-complexity implementation. In this paper, we study the problem of DoA estimation from one-bit measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 69 publications
(139 reference statements)
0
29
0
Order By: Relevance
“…We note that we have derived a closed-form expression for Σ by computing the fourth order moments of the orthant probability. Unfortunately, this closed-form expression is rather cumbersome and is derived for each element; we do not provide this expression of Σ due to the lack of space but we refer the interested readers to the journal extension of this work [29]. This closed form-expression shows that Σ is only a function of r.…”
Section: Asymptotic Performance Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We note that we have derived a closed-form expression for Σ by computing the fourth order moments of the orthant probability. Unfortunately, this closed-form expression is rather cumbersome and is derived for each element; we do not provide this expression of Σ due to the lack of space but we refer the interested readers to the journal extension of this work [29]. This closed form-expression shows that Σ is only a function of r.…”
Section: Asymptotic Performance Analysismentioning
confidence: 99%
“…Particularly, use of one-bit ADCs has received the most attention since they allow for sampling at an extremely high rate with a low cost and low power consumption. Recently, the problem of DoA estimation from one-bit data has gained considerable interest in the literature [22][23][24][25][26][27]. This problem has been investigated in [22][23][24][25] when a ULA is employed and it has been shown that one-bit quantization leads to a moderate performance loss compared to the case where infinite-bit quantized data is used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covariance matrix recovery plays an important role in statistical signal processing applications such as directions of arrival (DOA) estimation, radar waveform design, target parameter estimation, communication channel estimation, and adaptive radar detection [3]- [10]. When digital signal processing is concerned, using one-bit quantization and digitization, in which the input signals are compared with given threshold levels, allows for sampling at a very high rate and with lower energy consumption [11]- [14]. As a result of employing one-bit sampling, however, we can only use the sign data as partial available information to recover the signal covariance, and second order statistics in general, making it more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…One-bit ADCs represent each sample of the analog array observations with only a single bit offering, an exceedingly high sampling rate at a low production cost and very low power consumption [16]. The analytical performance bounds for DoA estimation from one-bit data have been studied in [28][29][30]. Further, a number of one-bit DoA estimators have been provided in [23][24][25]27], which rest on retrieving the covariance matrix of unquantized array observations using the well-known Bussgang theorem [31].…”
Section: Introductionmentioning
confidence: 99%